Contact Angle Measurement on Medical Implant Titanium Based Biomaterials. (2016) - Strnad, Gabriela; Chirila, Nicolae; Petrovan, Cecilia; Russu, Octav
Abstract: The aim of present research was to study the effect of some surface modification processes on wettability of Ti6Al4 V surfaces for medical implants quantified by using the measurement of contact angle. The surface modification procedures of several disc samples were performed by sand blasting, acid etching, passivation, and their combinations. Sand blasting was done with 250...300 μm SiO2 large grits. The acid etching process was performed in a dual bath of H2 SO4 1n and HCl 1n (1:1) at different elevated temperatures (60 °C, 80 °C, and 100 °C) using different process durations (1 h, 3 h, 6 h, 12 h, and 24 h). Passivation was done in 30% HNO3 at room temperature. On modified surfaces we evaluated topography, by measuring roughness, and analyzing scanning electron micrographs. Contact angle was measured using static method and direct measurement of the tangent angle at the three-phase contact point on a sessile drop proﬁle. We found that the influence of sand blasting prior to acid etching at low temperature (60 °C) on contact angle is beneficial when using long acid etching times (12 h and 24 h). Increasing the process time for acid etching leads to a decrease in contact angle which is a desired result. Increasing the temperature of acid etching bath leads to an increase in contact angle, thus decreasing the wettability. The passivation treatment leads to an increase of contact angle on sand blasted surfaces, lowering the hydrophilic properties of surfaces, and does not influence significantly the contact angle on surface without sand blasting treatment. The best preparation procedure, in terms of wettability measured by contact angle, was found to be sand blasting, followed by acid etching in above mentioned dual acid bath at 60 °C for 24 hours. In this case we measured a contact angle of 46° showing good hydrophilic properties.